Quantifying the causal strength of multivariate cardiovascular couplings with momentary information transfer. (23rd March 2015) - Runge, Jakob; Riedl, Maik; Müller, Andreas; Stepan, Holger; Kurths, Jürgen; Wessel, Niels
Abstract: This article studies a recently introduced information-theoretic approach to detect and quantify the causal couplings in a complex cardiovascular system. In the first step a causal algorithm detects the coupling delays and in the second step the causal strength of each coupling mechanism is quantified using the recently introduced momentary information transfer. As an example, the method is applied to time series of respiration, systolic and diastolic blood pressure, and heart rate of pregnant healthy women and women suffering from pre-eclampsia. A possible explanation for the influence of heart rate on systolic blood pressure is found and some differences between healthy women and patients are discussed.